Fair trade: A profitable trade - Uzan-Tidhar, Yael; Castellanos, Claudia (Technical Centre for Agricultural and Rural Cooperation, 2008)
Profi ts from fair trade products made by women in rural Swaziland go back to the communities to support some very innovative small-business schemes.